The Tourism Contribution Of Istana Siak Sri Indrapura To The Community Economy Of Siak District In Siak Regency, Riau Province, Indonesia - Winda Ningsih; Myrza Rahmanita (SEAN Institute, 2024)
Istana Siak is an heritage site of the Sultan Syarif Eunuch's official residence which is used as a historical tourism destination in Siak District, Siak Regency, Riau Province. This research is motivated by an increase in the number of tourist visits but the impact on the community's economy This research aims to explore the contribution of tourism to the community’s economy. This research method is quantitative descriptive. Respondents in this study were 100 tourists, 24 businessman and 15 workers. Data collected were analyzed by using multiplier effects through the calculation of calcultae the ratio of Keynesian multiplier effects and income ratio multiplier types I & II. The results showed that the contribution of tourism in the Siak palace has low contribution known from the local income multiplier value of 0.84, which means an increase in tourist spending by 100,000.- will have an impact on increasing the income of local people by Rp.84,000. It is recommended that all stakeholders synergize in their role in developing Siak tourism in a more integrated and integrated manner to increase the contribution of the Siak Palace to the community's economy.